A novel splice variant of Argonaut 2 affects microRNA target genes and cell viability of melanoma cells - Linck-Paulus, Lisa; Horn, Angelika; Matthies, Alexander Oliver; Fischer, S.; Meister, G.; Sticht, Heinrich; Kappelmann-Fenzl, M.; Boßerhoff, Anja Katrin (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2022)
CRIS-Team WoS Importer:2022-09-23

A previously unknown Argonaute 2 variant positively modulates the viability of melanoma cells - Linck-Paulus, Lisa; Meißgeier, Tina; Pieger, Katharina; Horn, Anselm; Matthies, Alexander Oliver; Fischer, Stefan; Meister, Gunter; Sticht, Heinrich; Kappelmann-Fenzl, Melanie; Boßerhoff, Anja Katrin (Cellular and Molecular Life Sciences, 2022)
In malignant melanoma, a highly aggressive form of skin cancer, many microRNAs are aberrantly expressed contributing to tumorigenesis and progression. Further, deregulation of microRNA processing enzymes, like the miRNA-binding protein Argonaute 2, significantly impacts microRNA function. This study characterizes a novel splice variant of Argonaut 2, AGO2-ex1/3. AGO2-ex1/3 is substantially expressed in different melanoma cell lines and patient-derived tissue samples. It is a mature mRNA, which is translated into an N-terminally truncated Argonaute 2 protein form. Molecular dynamics simulations show that the PAZ, MID, and PIWI domain largely retain their structure in AGO2-ex1/3 and that the truncation of the N-terminus leads to an increased interdomain flexibility. Expression of AGO2-ex1/3 provides a survival advantage for melanoma cells while the knockdown causes significantly reduced proliferation and increases apoptosis. RNA-sequencing revealed that in cells lacking AGO2-ex1/3 expression many miRNA target genes are deregulated, implicating a considerable role of AGO2-ex1/3 for miRNA function. This study inaugurates insights into an important role of a so far unknown splice variant of Argonaute 2 for the miRNA pathway as well as the mechanisms which drive growth and survival of melanoma cells. This knowledge provides the basis for potential new promising therapeutic targets focusing on small RNA-mediated gene regulation in melanoma.
CRIS-Team Scopus Importer:2022-08-19
Keywords: Alternative splicing; Argonaute 2; Melanoma; miRNAs

C-Jun drives melanoma progression in PTEN wild type melanoma cells - Kappelmann-Fenzl, Melanie; Gebhard, Claudia; Matthies, Alexander Oliver; Kuphal, Silke; Rehli, Michael; Boßerhoff, Anja Katrin (Cell Death & Disease, 2019)
Due to the critical impact of active AP-1 transcription factors in melanoma, it is important to define their target genes and to identify and ultimately inhibit oncogenic signals. Here we mapped the genome-wide occupancy of the AP-1 family member c-Jun in different melanoma cells and correlated AP-1 binding with transcriptome data to detect genes in melanoma regulated by c-Jun. Our analysis shows that c-Jun supports the malignant phenotype by deregulating genes in cancer-relevant signaling pathways, such as mitogen-activated protein kinase (MAPK) and phosphatidylinositol-3-kinase (PI3K) pathways. Moreover, we demonstrate that the importance of c-Jun depends on melanoma stage and mutation status of the tumor suppressor PTEN. Our study reveals that activation of c-Jun overrules the tumor suppressive effect of PTEN in early melanoma development. These findings help to understand the relevance of c-Jun within cancer pathways in different melanoma cell types, especially in relation to MAPK and PI3K pathways, which are commonly deregulated in melanomas. Consequently, targeting c-Jun in PTEN+ melanoma cells may represent a promising therapeutic strategy to inhibit survival of melanoma cells to prevent the development of a metastatic phenotype.
CRIS-Team Scopus Importer:2019-08-13

Dendritic Cells Are Dispensable for T Cell Priming and Control of Acute Lymphocytic Choriomeningitis Virus Infection - Hilpert, Cornelia; Sitte, Selina; Matthies, Alexander Oliver; Vöhringer, David (Journal of Immunology, 2016)
Dendritic cells (DCs) are considered to be the major APCs with potent activity for priming of naive CD4 and CD8 T cells. However, T cell priming can also be achieved by other APCs including macrophages, B cells, or even nonhematopoietic cell types. Systemic low-dose infection of mice with lymphocytic choriomeningitis virus (LCMV) results in massive expansion of virus-specific CD4 and CD8 T cells. To determine the role of DCs as APCs and source of type I IFNs in this infection model, we used ?DC mice in which DCs are constitutively ablated because of expression of the diphtheria toxin ? subunit within developing DCs. ?DC mice showed lower serum concentrations of IFN-? and IL-12p40, but normal IFN-? levels during the first days postinfection. No differences were found for proliferation of transferred TCR-transgenic cells during the early phase of infection, suggesting that T cell priming occurred with the same efficiency in wild-type and ?DC mice. Expansion and cytokine expression of endogenous LCMV-specific T cells was comparable between wild-type and ?DC mice during primary infection and upon rechallenge of memory mice. In both strains of infected mice the viral load was reduced below the limit of detection with the same kinetic. Further, germinal center formation and LCMV-specific Ab responses were not impaired in ?DC mice. This indicates that DCs are dispensable as APCs for protective immunity against LCMV infectio
EVALuna2:25882

HDAC2 Is Involved in the Regulation of BRN3A in Melanocytes and Melanoma - Heppt, Markus; Wessely, Anja; Hornig, Eva; Kammerbauer, Claudia; Graf, Saskia A.; Besch, Robert; French, Lars E.; Matthies, Alexander Oliver; Kuphal, Silke; Kappelmann-Fenzl, Melanie; Boßerhoff, Anja Katrin; Berking, Carola (International Journal of Molecular Sciences, 2022)
The neural crest transcription factor BRN3A is essential for the proliferation and survival of melanoma cells. It is frequently expressed in melanoma but not in normal melanocytes or benign nevi. The mechanisms underlying the aberrant expression of BRN3A are unknown. Here, we investigated the epigenetic regulation of BRN3A in melanocytes and melanoma cell lines treated with DNA methyltransferase (DNMT), histone acetyltransferase (HAT), and histone deacetylase (HDAC) inhibitors. DNMT and HAT inhibition did not significantly alter BRN3A expression levels, whereas panHDAC inhibition by trichostatin A led to increased expression. Treatment with the isoform-specific HDAC inhibitor mocetinostat, but not with PCI-34051, also increased BRN3A expression levels, suggesting that class I HDACs HDAC1, HDAC2, and HDAC3, and class IV HDAC11, were involved in the regulation of BRN3A expression. Transient silencing of HDACs 1, 2, 3, and 11 by siRNAs revealed that, specifically, HDAC2 inhibition was able to increase BRN3A expression. ChIP-Seq analysis uncovered that HDAC2 inhibition specifically increased H3K27ac levels at a distal enhancer region of the BRN3A gene. Altogether, our data suggest that HDAC2 is a key epigenetic regulator of BRN3A in melanocytes and melanoma cells. These results highlight the importance of epigenetic mechanisms in regulating melanoma oncogenes.
CRIS-Team Scopus Importer:2022-02-04
Keywords: BRN3A; ChIP-Seq; DNA methylation; Epigenetic regulation; HAT; HDAC; Melanoma

Knockdown of Lamin B1 and the Corresponding Lamin B Receptor Leads to Changes in Heterochromatin State and Senescence Induction in Malignant Melanoma - Lämmerhirt, Lisa; Kappelmann-Fenzl, Melanie; Fischer, Stefan; Pommer, Michaela; Zimmermann, Tom; Kluge, Viola; Matthies, Alexander Oliver; Kuphal, Silke; Boßerhoff, Anja Katrin (Cells, 2022)
Modifications in nuclear structures of cells are implicated in several diseases including cancer. They result in changes in nuclear activity, structural dynamics and cell signalling. However, the role of the nuclear lamina and related proteins in malignant melanoma is still unknown. Its molecular characterisation might lead to a deeper understanding and the development of new therapy approaches. In this study, we analysed the functional effects of dysregulated nuclear lamin B1 (LMNB1) and its nuclear receptor (LBR). According to their cellular localisation and function, we revealed that these genes are crucially involved in nuclear processes like chromatin organisation. RNA sequencing and differential gene expression analysis after knockdown of LMNB1 and LBR revealed their implication in important cellular processes driving ER stress leading to senescence and changes in chromatin state, which were also experimentally validated. We determined that melanoma cells need both molecules independently to prevent senescence. Hence, downregulation of both molecules in a BRAFV600E melanocytic senescence model as well as in etoposide-treated melanoma cells indicates both as potential senescence markers in melanoma. Our findings suggest that LMNB1 and LBR influence senescence and affect nuclear processes like chromatin condensation and thus are functionally relevant for melanoma progression.
CRIS-Team Scopus Importer:2022-08-05
Keywords: chromatin state; heterochromatin foci; LBR; LMNB1; melanoma; nuclear lamina; senescence

Molecular changes induced in melanoma by cell culturing in 3D alginate hydrogels - Kappelmann-Fenzl, M.; Schmidt, Sonja; Fischer, Stefan; Schmid, Rafael; Lämmerhirt, Lisa; Fischer, Lena; Schrüfer, Stefan; Thievessen, Ingo; Schubert, Dirk W.; Matthies, Alexander Oliver; Detsch, Rainer; Boccaccini, Aldo R.; et al. (Cancers, 2021)
Alginate hydrogels have been used as a biomaterial for 3D culturing for several years. Here, gene expression patterns in melanoma cells cultivated in 3D alginate are compared to 2D cultures. It is well-known that 2D cell culture is not resembling the complex in vivo situation well. However, the use of very intricate 3D models does not allow performing high-throughput screening and analysis is highly complex. 3D cell culture strategies in hydrogels will better mimic the in vivo situation while they maintain feasibility for large-scale analysis. As alginate is an easy-to-use material and due to its favorable properties, it is commonly applied as a bioink component in the growing field of cell encapsulation and biofabrication. Yet, only a little information about the transcriptome in 3D cultures in hydrogels like alginate is available. In this study, changes in the transcriptome based on RNA-Seq data by cultivating melanoma cells in 3D alginate are analyzed and reveal marked changes compared to cells cultured on usual 2D tissue culture plastic. Deregulated genes represent valuable cues to signaling pathways and molecules affected by the culture method. Using this as a model system for tumor cell plasticity and heterogeneity, EGR1 is determined to play an important role in melanoma progression.
CRIS-Team Scopus Importer:2021-08-20
Keywords: 3D cultivation; Biomaterials; EGR1; Melanoma; Whole transcriptome